Synthesis, Properties and Applications of Ultrananocrystalline Diamond Proceedings of the NATO ARW on Synthesis, Properties and Applications of Ultrananocrystalline Diamond, St. Petersburg, Russia, from 7 to 10 June 2004. - Gruen, Dieter M.; Shenderova, Olga A.; Vul', Alexander Ya.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2005)
We are pleased to present the Proceedings of the NATO Advanced Research Workshop “Syntheses, Properties and Applications of Ultrananocrystalline Diamond” which was held June 7-10, 2004 in St. Petersburg, Russia. The main goal of the Workshop was to provide a forum for the intensive exchange of opinions between scientists from Russia and NATO countries in order to give additional impetus to the development of the science and applications of a new carbon nanostructure, called ultrananocrystalline diamond (UNCD) composed of 2-5 nm crystallites. There are two forms of UNCD, dispersed particles and films. The two communities of researchers working on these two forms of UNCD have hitherto lacked a common forum in which to explore areas of scientific and technological overlap. As a consequence, the two fields have up to now developed independently of each other. The time had clearly come to remedy this situation in order to be able to take full advantage of the enormous potential for societal benefits to be derived from exploiting the synergistic relationships between UNCD dispersed particulates and UNCD films. The NATO sponsored ARW therefore occurred in a very timely manner and was successful in beginning the desired dialogue, a precondition for making progress toward the above stated goal. The discovery of UNCD completes a triadof nanostructured carbonswhich includes fullerenes and nanotubes.
New Forms of Nanocarbon. Theory and Observation -- Carbon Family at the Nanoscale -- Structural and Electronic Properties of Isolated Nanodiamonds: A Theoretical Perspective -- From Nanodiamond to Nanowires -- Quantum Chemical Studies of Growth Mechanisms of Ultrananocrystalline Diamond -- Nanodiamonds in the Cosmos -- Diamond Molecules Found in Petroleum -- Ultrananocrystalline Diamond Films -- Synthesis of Nanocrystalline Diamond Films in Ar/H2/CH4 Microwave Discharges -- Modelling of Ar/H2/CH4 Microwave Discharges Used for Nanocrystalline Diamond Growth -- Nanodiamond Seeding for Nucleation and Growth of CVD Diamond Films -- Mechanism and Properties of Nanodiamond Films Deposited by the DC-GD-CVD Process -- Nanodiamond Injection into the Gas-Phase During CVD Diamond Film Growth -- Stabilization of Diamond-Like Nanoclusters by Metallic Atoms and the Epitaxial Growth of Diamond Films: ab initio Simulation -- Detonation nanodiamond -- The Formation Kinetics of Detonation Nanodiamonds -- Nanocarbon Phase Diagram and Conditions for Detonation Nanodiamond Formation -- Nanodiamond Graphitization and Properties of Onion-Like Carbon -- Physical and Chemical Problems of Modification of Detonation Nanodiamond Surface Properties -- Disintegration and Purification of Crude Aggregates of Detonation Nanodiamond -- Purification and Functionalization of Nanodiamond -- Interaction of Carbon Atoms with Nanodiamond Surface -- Physical and Chemical Properties of Modified Nanodiamonds -- Magnetic Resonance Study of Nanodiamonds -- Infrared Spectra of Explosion Nanodiamonds: A Comparison with Spectra of Hydrogenated Amorphous Carbon Films -- Conversion of Elemental Substances and Inorganic Compounds to Carbon Nanostructures -- The Fine and Fractal Structure and Protonic Conductivity of Phosphosilicate-Diamond Sol-Gel Nanocomposites -- Facilities for Ultradisperse Diamond Production -- Ultradisperse Diamond Regeneration from Composite Electrolytes of Chromium Plating -- Synthesis and Processing of the Chelyabinsk Detonation Nanodiamonds -- Conversion Raw Materials in Industrial Production of Ultradisperse Diamonds -- Ultradisperse Diamond Modifications in the Composite Gilding Process -- Applications of Nanodiamond -- Applying CVD Diamond and Particulate Nanodiamond -- Electronic Properties and Applications of Ultrananocrystalline Diamond -- Thermoelectric Effect in Field Electron Emission from Nanocarbon.
Keywords: Condensed matter; Nanotechnology; Materials—Surfaces.; Thin films; Physics; Engineering; Condensed Matter Physics; Nanotechnology; Surfaces and Interfaces, Thin Films; Physics, general; Engineering, general